2023
DOI: 10.3390/biomedicines11092517
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Surfactant Protein D: A Biomarker for Acute Lung Injury?

Alyssa Elmore,
Ali Almuntashiri,
Xiaoyun Wang
et al.

Abstract: Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are life-threatening lung diseases in critically ill patients. The lack of prognostic biomarkers has halted detection methods and effective therapy development. Quantitative biomarker-based approaches in the systemic circulation have been proposed as a means of enhancing diagnostic strategies as well as pharmacotherapy in a patient-specific manner. Pulmonary surfactants are complex mixtures made up of lipids and proteins, which are secreted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Several studies show that SP-D levels can increase in patients with ARDS. 35,36 Increased serum receptor for advanced glycation endproducts (sRAGE) can be an indicator in the development of ARDS or related to the severity of ARDS events. Several studies have shown that sRAGE levels may be increased in the setting of ARDS, particularly in patients with higher ARDS severity.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies show that SP-D levels can increase in patients with ARDS. 35,36 Increased serum receptor for advanced glycation endproducts (sRAGE) can be an indicator in the development of ARDS or related to the severity of ARDS events. Several studies have shown that sRAGE levels may be increased in the setting of ARDS, particularly in patients with higher ARDS severity.…”
Section: Discussionmentioning
confidence: 99%